The Impact of Anxiety, Depression, and Stress on Emotional Stability among the University Students from the view of educational aspects - ALI AHMED, Shahla (2020)
In the contemporary society, depression, anxiety, and stress are much more common than it was in history. The recent studies have outlined that the young adults are experiencing depression and anxiety disorders that is affecting their emotional and mental well-being.  Aim of this co-relational survey model study is to investigate the impact of anxiety, depression and stress on emotional stability in terms of gender, age, year of study, department and place they stay. The study adapted pre-designed questionnaires to collect data. The sample of the study consists of approximately 260 undergraduate university students from University of Sulaymaniyah in Northern Iraq. The researcher adapted two scales first Henry and Crawford scale that call DASS for measuring the level of anxiety, depression, and stress and second one to measure Emotional stability using a self-reported scale. The collected data was analyzed using SPSS version 22 to find result for this thesis. The results of the study outlined that there is a negative but significant correlation among depression, anxiety, and stress with emotional stability. Also there is no significant relationship between emotional stability in terms of gender and age, other findings of the study show that DASS has no significant relationship with age, and year of study and place of stay in generally, but there a significant difference between DASS in terms of gender and department.